Drug Resistance Mechanisms in Bacteria Causing Sexually Transmitted Diseases and Associated with Vaginosis - Shaskolskiy, Boris; Dementieva, Ekaterina; Leinsoo, Arvo; Runina, Anastassia; Vorobyev, Denis; Plakhova, Xenia; Kubanov, Alexey; Deryabin, Dmitrii; Gryadunov, Dmitry (Frontiers in Microbiology, 2016)
Here, we review sexually transmitted diseases (STDs) caused by pathogenic bacteria and vaginal infections which result from an overgrowth of opportunistic bacterial microflora. First, we describe the STDs, the corresponding pathogens and the antimicrobials used for their treatment. In addition to the well-known diseases caused by single pathogens (i.e., syphilis, gonococcal infections, and chlamydiosis), we consider polymicrobial reproductive tract infections (especially those that are difficult to effectively clinically manage). Then, we summarize the biochemical mechanisms that lead to antimicrobial resistance and the most recent data on the emergence of drug resistance in STD pathogens and bacteria associated with vaginosis. A large amount of research performed in the last 10-15 years has shed light on the enormous diversity of mechanisms of resistance developed by bacteria. А detailed understanding of the mechanisms of antimicrobials action and the emergence of resistance is necessary to modify existing drugs and to develop new ones directed against new targets.